Hubungan Dukungan Keluarga Terhadap Kualitas Hidup Pasien Kanker Payudara di Rumah Sakit Islam Siti Khodijah Palembang Tahun 2018 - Yofa Anggriani Utama (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Cancer is one of the causes of death in both developed and developing countries, cancer is increasing in developing countries due to increasing lifestyle, breast cancer is a cancer that causes death in women in the world, breast cancer is the highest contributor to mortality in women in the world, 43.3 per 100,000. The purpose of this study was to determine the relationship of family support to the quality of life of breast cancer patients. The research design used was observational analytic with cross sectional approach. The sampling technique used purposive sampling technique, the study sample amounted to 63 breast cancer patients. The results show that there is a relationship between family support and the quality of life of breast cancer patients with a p value of 0.032. shows there is a relationship between family support for the quality of life of patients with breast cancer. Suggestions that nurses can improve the quality of nursing services, and provide motivation to patients and families of breast cancer in carrying out breast cancer treatment.